On the Relation between Financial Reporting Quality and Country Attributes: Research Challenges and Opportunities - Isidro, Helena; Nanda, Dhananjay (DJ); Wysocki, Peter D. (The Accounting Review, 2020)
ABSTRACT We provide new evidence on the codependence among the many country attributes previously linked to financial reporting quality. First, we show that the synchronicity of 21 changing country attributes spikes surrounding mandatory IFRS adoption. Thus, while IFRS adoption “explains” increased reporting quality, this finding disappears after including other changing country determinants of reporting quality. Second, a single underlying factor distills the numerous reporting quality measures used in the international literature. Finally, we document that four underlying country factors largely subsume the individual explanatory power of 72 candidate country attributes in explaining reporting quality levels across countries. We conclude with implications and suggestions for future research on international reporting quality. JEL Classifications: F30; G15; K22; M41. Data Availability: Data used in this paper are from publicly available sources and/or are drawn directly from data tabulated in published research papers.